STATUS KEBERLANJUTAN KAWASAN LUBUK LARANGAN DI DESA PANGKALAN INDARUNG, KABUPATEN KUANTAN SINGINGI - M. Subkhan Riza; Zulkarnaini Zulkarnaini; Efriyeldi Efriyeldi (Jurnal Ilmu Lingkungan, 2019)
The purpose of this study was to analyze the sustainability status of the Lubuk larangan area and find out the sensitive attributes of the sustainability of the Lubuk larangan area in Pangkalan Indarung Village, Kuantan Singingi Regency. This research was conducted in Pangkalan Indarung Village, Kuantan Singingi Regency from October 2017 to March 2018. The method used was the survey method. The research uses Rapfish analysis and analytic hierarchy process (AHP). Rapfish (Rapid Appraisal for Fisheries) is an analytical technique to evaluate the sustainability of a multidisciplinary region. The sustainability status of the Lubuk larangan area in Pangkalan Indarung Village, Kuantan Singingi Regency is in a fairly sustainable category with an index value of 70.75. Based on the analysis of each dimension, it shows that the economic dimension has the lowest sustainability index value of 53.65 or is in a fairly sustainable category. While the other four dimensionns are in good or sustainable status, namely institutional dimensions (82.03), ecological dimensions (76.16), technological dimensions (75.89) and socio-cultural dimensions (75.09). Attributes that are sensitive to the Lubuk laranganarea sustainability index are; changes in forest land cover, protected area, captured species diversity, alternative livelihoods, income changes, community empowerment, types of fishing gear, formal institutional roles, and management rules.